Preparation, characterization, electrical conductivity, and life cycle assessment of carbon nanofibers-reinforced Ecuadorian natural zeolite-based geopolymer composites - Adriana Alvarado; Haci Baykara; Ariel Riofrio; Mauricio Cornejo; Wilson Merchan-Merchan (Heliyon, 2024)
Geopolymers are inorganic crosslinked polymers with much less carbon footprint than ordinary Portland cement. Geopolymers and geopolymer-based materials have superior mechanical and durability properties with extreme thermal and chemical resistance. Carbon nano- or microfibers-reinforced geopolymers show potential properties such as electric conductivity, enhanced mechanical and thermal stability, and multi-functionality. This study evaluated the effect of incorporating carbon nanofibers in natural zeolite-based geopolymers and their impact on the mechanical, thermal, and electric conductivity of yielded geopolymer composites. Additionally, a life cycle assessment for 1 m3 geopolymer and its carbon fiber reinforced geopolymers’ production has been conducted to evaluate the environmental impact of the processes.